2022
DOI: 10.3389/fphar.2022.967633
|View full text |Cite
|
Sign up to set email alerts
|

PARP inhibitor resistance in breast and gynecological cancer: Resistance mechanisms and combination therapy strategies

Abstract: Breast cancer and gynecological tumors seriously endanger women’s physical and mental health, fertility, and quality of life. Due to standardized surgical treatment, chemotherapy, and radiotherapy, the prognosis and overall survival of cancer patients have improved compared to earlier, but the management of advanced disease still faces great challenges. Recently, poly (ADP-ribose) polymerase (PARP) inhibitors (PARPis) have been clinically approved for breast and gynecological cancer patients, significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 153 publications
0
15
0
Order By: Relevance
“…Mechanisms contributing to resistance to PARPi in BRCA1 mutated cells are (I) increase in drug efflux, (II) restoration of HR, (III) decreased PARP1 trapping, and (IV) stabilization of stalled DNA replication forks [ 9 , 48 ]. All BRCA1 mutated clones still show residual HR activity, most strongly in the MMC- and PAPR1i-resistant BRCA1 exon-9.2 clone, contributing to the observed resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms contributing to resistance to PARPi in BRCA1 mutated cells are (I) increase in drug efflux, (II) restoration of HR, (III) decreased PARP1 trapping, and (IV) stabilization of stalled DNA replication forks [ 9 , 48 ]. All BRCA1 mutated clones still show residual HR activity, most strongly in the MMC- and PAPR1i-resistant BRCA1 exon-9.2 clone, contributing to the observed resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the involvement of BRCA1 in all the key steps of HR, a loss of BRCA1 can lead to a HR-deficiency (HRD) [ 7 , 8 ]. Several studies showed that overexpression of other involved DNA damage response (DDR) or HR proteins can at least partially compensate for the loss and restore the function of HR [ 9 , 10 ]. A defect in HR is associated with an increased sensitivity to platinum-based chemotherapies and PARP1 inhibitors in a synthetic lethal manner, though not always resulting in improved patient survival [ 5 , 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has offered a therapeutic vulnerability that has been extensively explored clinically in BRCA1/2 mutant patients but is now also being examined as a viable therapy in tumours with other specific genotypes, including those presenting with ATM , PALB2 , RAD51C , and RAD51D mutations [ 117 ]. As mentioned previously, the major drawback of PARP inhibitors is the rapid onset of acquired resistance which is mediated through multiple mechanisms [ 118 ]. A better understanding of this will lead to novel therapeutic approaches that harness the power of drug targeting PARP enzymes, increasing the repertoire of potential therapeutic targets for CSCs.…”
Section: The Dna Damage Response (Ddr)mentioning
confidence: 99%
“…Ovarian (OC), cervical (CC), and endometrial cancer (EC) are the most common gynecological cancers in the female reproductive system ( 1 , 2 ). OC is the most lethal gynecological malignancy in developed countries ( 3 ), with a 5-year survival rate of ~47% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%